Medicaid expansion and neonatal outcomes in Oregon. Issue 5 (8th December 2020) - Harvey, S. Marie; Gibbs, Susannah; Oakley, Lisa; Luck, Jeff; Yoon, Jangho
Abstract: Rationale, aims and objectives: Low‐income women disproportionately experience preventable, adverse neonatal outcomes. Prior to the Affordable Care Act (ACA) Medicaid expansion, many low‐income women became eligible for coverage only after becoming pregnant, reducing their access to healthcare before pregnancy and creating discontinuities in care that may delay Medicaid enrollment. The objective of this study was to examine the impact of the ACA Medicaid expansion on neonatal outcomes among low‐income populations in Oregon. Method: We used linked Oregon birth certificate and Medicaid data from 2008‐2016 to identify control and policy groups of women who gave birth both before and after implementation of the ACA Medicaid expansion (n = 21 204 births to N = 10 602 women). We conducted a difference‐in‐differences analysis of the effect of Medicaid expansion on preterm birth, low birthweight (LBW), neonatal intensive care unit (NICU) admissions, and neonatal mortality. Results: We found policy effects on reducing LBW (interaction aOR = 0.71, 95% CI: 0.57‐0.90) and preterm birth (interaction aOR 0.77, 95% CI: 0.62 = 0.96) but not on NICU admissions or neonatal mortality. Conclusions: This study provides evidence that expanding Medicaid coverage may have positive effects on LBW and preterm birth, which could lead to important long‐term impacts on childhood and later‐life health outcomes. States that have not expanded their Medicaid programs might improve neonatal outcomes among low‐income populations by extending insurance coverage to low‐income adults.